ANALISIS FAKTOR PREDIKTOR MEROKOK PADA REMAJA DI KOTA DEPOK TAHUN 2019 ANALYSIS OF PREDICTORS OF SMOKING IN ADOLESCENTS IN DEPOK CITY IN 2019 - Fitriani, Nur Laela; Nurrizka, Rahmah Hida (Journal of Religion and Public Health, 2020)
Smoking is a public health concern because it leads to a variety of illnesses and even death. The number of smokers in Indonesia from year to year tends to increase. In addition, age started smoking in Indonesia is relatively young. The aims of the present study were to determine the prevalence of smoking action in adolescents of Depok. This study uses a quantitative method with a cross sectional study design with a sample of 415 students. Samples were taken at purposive and the sample size for each school is determined in proportion. The results of this study found that there are gender (p-value 0,001; OR=9,22; 95% CI=3,49-24,34), psychological reasons; want to try smoking (p-value 0,001; OR= 5,67; 95% CI= 2,23-14,38), affordability of access to cigarettes (p-value 0,001; OR= 45,15; 95% CI= 14,77-138,01), and the influence of cigarette advertising (p-value 0,001; OR= 18,59; 95% CI= 4,83-71,53). The best predictors of this study are affordability of access to cigarettes and the influence of cigarette advertising. Based on the results of research to protect adolescents, it is recommended to include the smoking hazard curriculum in counseling guidance lessons and optimize the smoke-free area regulations in the school environment by giving sanctions if the rules are violated.AbstrakMerokok merupakan masalah kesehatan masyarakat karena menyebabkan berbagai penyakit dan bahkan kematian. Jumlah perokok di Indonesia dari tahun ke tahun cenderung meningkat. Selain itu, usia mulai merokok di Indonesia relatif masih muda. Tujuan dari penelitian ini adalah untuk mengetahui prevalensi tindakan merokok pada remaja Depok. Penelitian ini menggunakan metode kuantitatif dengan desain penelitian cross sectional dengan sampel sebanyak 415 siswa. Sampel diambil secara purposive dan besar sampel untuk setiap sekolah ditentukan secara proporsional. Hasil penelitian ini ditemukan bahwa ada jenis kelamin (p-value 0,001; OR=9,22; 95% CI=3,49-24,34), alasan psikologis; ingin mencoba merokok (p-value 0,001; OR= 5,67; CI 95%= 2,23-14,38), keterjangkauan akses terhadap rokok (p-value 0,001; OR= 45,15; CI 95%= 14,77-138.01), dan pengaruh iklan rokok (p-value 0,001; OR= 18,59; 95% CI= 4,83-71,53). Prediktor terbaik dari penelitian ini adalah keterjangkauan akses terhadap rokok dan pengaruh iklan rokok. Berdasarkan hasil penelitian untuk melindungi remaja, disarankan untuk memasukkan kurikulum bahaya merokok dalam pelajaran bimbingan konseling dan mengoptimalkan peraturan kawasan bebas rokok di lingkungan sekolah dengan memberikan sanksi jika peraturan dilanggar.